Hierarchically Micro- and Nanostructured Polymer via Crystallinity Alteration for Sustainable Environmental Cooling - Shi, Changmin (Langmuir : the ACS journal of surfaces and colloids, 2024)
Cooling environments are a pervasive need in our society, with conventional air conditioners being the most popular approach. However, air conditioners rely heavily on electricity and Freon, a chemical that depletes ozone and contributes to greenhouse gas effects. To address this issue, passive daytime radiative coolers (PDRCs) have been proposed to achieve cooling by simultaneously reflecting sunlight and allowing internal heat to escape without electricity. Despite their potential, most high-performance PDRCs are composed of thick polymer films, which increases material costs during PDRC preparation and limits thermal transport. In this work, we introduced an economical and scalable solvent evaporation-based method to prepare a relatively thin hierarchically micro- and nanostructured poly(vinylidene fluoride-trifluoroethylene) via crystallinity alteration. Particularly, we find that the key to generating nanosized pores is to remove the water residual within the film without sample annealing, which significantly enhances the scattering efficiency across the solar spectrum. With our design, we demonstrate effective cooling of the outdoor environment, achieving a cooling temperature of Δ2.5 °C, with a film thickness of only 215 μm. Furthermore, our model suggested that applying this material could lead to annual energy savings of up to ∼39% in warmer climates across the country and up to 715 GJ nationwide. Developing effective PDRCs with reduced material thickness, such as the one discussed here, is imperative for implementing sustainable cooling solutions and reducing our carbon footprint